1,2,3,4-Tetramethylcyclopent-2-ene-1,4-diol - Blaurock, Steffen (International Union of Crystallography, 2008)
The title compound, C(9)H(16)O(2), crystallizes with two molecules in the asymmetric unit. The structure displays intermolecular O—H⋯O hydrogen bonding.